A BRIEF REVIEW ABOUT INDICATORS TO TEST THE QUALITY OF WATER IN CUBAN SPRINGS - Valladares Fuente , Fernando Emilio (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2022)
This present study sets as an objective: to establish a brief review about some of the indicators that have been used in the world and specifically in Cuba to evaluate the quality of water in Springs. The author makes a logical transference of environmental components worldwide and nationwide to propose a group or integrated parameters that can be considered in Cuba according to the potentials and the specification of this Caribbean island. Springs in Cuba are characterized by being rich in mineral components because of the Mountain precedence of springs. Most of the water contamination has been related to the influence of Sugar Industry, misuse of Mining and a progressive advance of Salinization due to the impact of Climate Changes. Some of the springs contain ingredients very beneficial to health. In this paper there is a historical tendency to evaluate the situation of springs based only in physical, chemical and biological parameters. However, due to the anthropological incidence of Springs in its environmental deterioration, there is a necessary and strong claim of the socio environmental indicator. There comes up a balance of the most environmental parameter historically used and the necessity of empowering these parameters.